2014
DOI: 10.4103/0975-1475.127772
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Carabelli trait in children from Southern India - A cross sectional study

Abstract: Background:The distribution of the Carabelli trait is highly variable in different regions and races of the world.Objective:To determine the prevalence of Carabelli trait in a group of children from Nellore.Materials and Methods:Children who attended the department between October 2011 to March 2012 were selected and examined for the expression of Carabelli trait in the maxillary primary second molar, permanent first and permanent second molars on the basis of the classification developed by Kraus and standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 38 publications
11
19
0
5
Order By: Relevance
“…This trait was also observed in the permanent second molar in a few studies[ 5 7 10 ] However, this was not feasible in the present study due to age constraints. When the degree of expression of cusp of Carabelli in permanent maxillary first molar was taken into consideration, absence of trait was seen in 60.2%, a negative expression in 32.6%, and a positive expression in 6.8%.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…This trait was also observed in the permanent second molar in a few studies[ 5 7 10 ] However, this was not feasible in the present study due to age constraints. When the degree of expression of cusp of Carabelli in permanent maxillary first molar was taken into consideration, absence of trait was seen in 60.2%, a negative expression in 32.6%, and a positive expression in 6.8%.…”
Section: Discussionsupporting
confidence: 48%
“…The next trait in the order of prevalence was the cusp of Carabelli in primary second molar (40.3%), and subsequently the cusp of Carabelli in permanent first molar (39.7%). Literature is replete with studies[ 5 6 7 8 9 ] showing the prevalence of cusp of Carabelli in permanent and primary teeth ranging from 2.1–85.7% to 67.5–89.8%, respectively. The present study showed a prevalence percent in permanent teeth that fit well within the range, but in primary teeth it was comparatively lesser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, CT was found most frequently in first upper molars and was usually detected bilaterally. 3,4,10,[27][28][29] A correspondence between the higher prevalence of CT on 16/26 than on 17/27 and bilateralism is prominent in the literature, and this was found also to be the case in our study.…”
Section: Discussionsupporting
confidence: 84%